New Economic Geography and Regional Price Level - Reinhold Kosfeld; Hans-Friedrich Eckey; Matthias Türck (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2005)
In view of the lack of area-wide regional price data, Aten and Heston (2005) adopted an econometric approach in estimating regional price level from an international perspective. At a regional level, however, spatial economic theory may contribute to advancement in explaining price level determination. Recently, the market potential approach as an essential element of NEG models has been employed for explaining observed regional land prices (Brakman et al., 2004). The present paper relies on the price mechanisms of the Helpman model (Helpman, 1998) in developing spatial-econometric models for regional price level and its major components. By evaluating a south German sample, first evidence on the empirical significance of NEG-based price level models is provided.
Keywords: C21; R13; R31; 330; Regional price level; Helpman model; spatial-econometric models; ESDA; Neue ökonomische Geographie; Regionale Konzentration; Räumliche Preistheorie; Bayern